![image](https://tex.z-dn.net/?f=3x%5E2%2B2x-1+%3E+0+%5C%5C+D%3D4%2B12%3D16+%5C%5C+x_1%3D%5Cfrac%7B-2-4%7D%7B6%7D%3D-1+%5C%5C+x_2%3D%5Cfrac%7B-2%2B4%7D%7B6%7D%3D%5Cfrac%7B1%7D%7B3%7D+%5C%5C+3%28x%2B1%29%28x-%5Cfrac%7B1%7D%7B3%7D%29+%3E+0+)
0 \\ D=4+12=16 \\ x_1=\frac{-2-4}{6}=-1 \\ x_2=\frac{-2+4}{6}=\frac{1}{3} \\ 3(x+1)(x-\frac{1}{3}) > 0 " alt="3x^2+2x-1 > 0 \\ D=4+12=16 \\ x_1=\frac{-2-4}{6}=-1 \\ x_2=\frac{-2+4}{6}=\frac{1}{3} \\ 3(x+1)(x-\frac{1}{3}) > 0 " align="absmiddle" class="latex-formula">
---(+)--(○-1)--(-)----(○1/3)----(+)--->